Identification of the spatial causes of urban sprawl with the use of land information systems and GIS tools - Wolny Ada; Dawidowicz Agnieszka; Źróbek Ryszard (Bulletin of Geography. Socio-Economic Series)
Urbanization is one of the processes that determine the development of a country or a region, but it has both advantages and side effects. Some of its aspects may lead to unsustainable growth and dispersion of built–up area. The main causes of this process are increases in costs of transportation, infrastructure and nature conservation. There is a threat of uncontrolled spread of development as a result of urbanization processes, particularly in suburban municipalities. It has been requested by many researches that authorities put more interest in avoiding dispersed suburbanization, but they still are looking for better solutions, tools and procedures to solve this problem.